2006
DOI: 10.2146/ajhp050454
|View full text |Cite
|
Sign up to set email alerts
|

Safety of amiodarone in the prevention of postoperative atrial fibrillation: A meta-analysis

Abstract: Meta-analysis showed amiodarone to be associated with an increased risk of developing bradycardia and hypotension when used for the prophylaxis of postoperative atrial fibrillation. The greatest risk in the occurrence of these adverse events arose when using regimens containing i.v. amiodarone, initiating prophylaxis during the postoperative period, and using regimens with average daily doses exceeding 1 g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…By 'overlapping', it is meant that any one of these meta-analyses shares some trial results with at least one other of these metaanalyses, to the extent that the estimates produced by these meta-analyses may be regarded as being to some degree not independent of one another. For meta-analyses with non-fatal endpoints, there are 23 such overlapping metaanalyses [17,19,20,[26][27][28][30][31][32][33]35,[38][39][40][41][43][44][45][46][47][48][49][50]. Therefore, there are 18 meta-analyses with fatal endpoints [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] and 21 meta-analyses with non-fatal endpoints [15,22,25,42,[52][53]…”
Section: Resultsmentioning
confidence: 99%
“…By 'overlapping', it is meant that any one of these meta-analyses shares some trial results with at least one other of these metaanalyses, to the extent that the estimates produced by these meta-analyses may be regarded as being to some degree not independent of one another. For meta-analyses with non-fatal endpoints, there are 23 such overlapping metaanalyses [17,19,20,[26][27][28][30][31][32][33]35,[38][39][40][41][43][44][45][46][47][48][49][50]. Therefore, there are 18 meta-analyses with fatal endpoints [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] and 21 meta-analyses with non-fatal endpoints [15,22,25,42,[52][53]…”
Section: Resultsmentioning
confidence: 99%
“…10 A meta-analysis of randomized trials of amiodarone versus placebo for prevention of postoperative AF (n = 3,408) reported an increased risk of bradycardia and hypotension associated with amiodarone, especially when given intravenously. 11 Similarly, sotalol prophylaxis was associated with a higher prevalence of postoperative bradyarrhythmias, compared with metoprolol. 12 Comparably, atorvastatin (40 mg/day) started 7 days preoperatively, and continued in the postoperative period reduced postoperative AF by 61% in the ARMYDA-3 prospective randomized trial.…”
Section: Prevention Of Postoperative Af With Ivabradinementioning
confidence: 99%
“…A meta-analysis of 18 trials (3408 patients) performed to assess the safety of amiodarone to prevent atrial fibrillation after cardiac surgery found an increased risk for bradycardia and hypotension in the amiodaronetreated group but no other statistically significant differences in other measured end points (heart block, myocardial infarction, stroke, and death). 28 These findings were most apparent in patients treated with high doses (>1 g per day), with intravenous formulations, and when initiated in the postoperative period.…”
Section: Amiodaronementioning
confidence: 99%